Finding out learning (curves, equations and rates) for constructional work activities in Iraq and comparing them with a neighboring country (Syria) - Ibrahim A. Mohammed, Dr. (Iraqi Journal of Civil Engineering, 2016)
Very little attention was given to study learning curves phenomenon in the construction industry, for many reasons related to the nature of production in this industry and also because of the variety of factors which affect these works. This research aims to measure the amount of improvement in the acquired production by the workers on the repeated construction operation because of the experience and learning in Iraq compared with a neighboring country (Syria).The measurement technique involves recording the time required to achieve every unit and finding out the mathematical relation which represents the learning curve for each item of production. The study involves six items (activities) of construction as follows: 1- Ceramic tiles (20 × 20 cm) for walls. 2- Paving the pavement of the street with concrete blocks. 3- Tiling the rooms with mosaic (30 × 30 cm). 4- Building the walls with concrete blocks (20 × 20 × 40 cm). 5- Coating the walls with emulsion paints. 6- Finishing the walls with gypsum The most important results of the research are that the amount of learning varies from 4.2% to 8.6% in Iraq, and 3.3% to 11.8% in Syria, which considered little compared to the developed countries.